2008
DOI: 10.1111/j.1747-0285.2007.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Crystal Structures of LXRβ in Relation to Plasticity of the Ligand‐Binding Domain upon Ligand Binding

Abstract: Liver X receptors (LXRs) are a member of the nuclear hormone receptor superfamily of ligand activated transcription factors. LXRs have gained importance as therapeutic targets because of their involvement in many diseases. Analysis of the protein-ligand complexes of X-ray crystallography-derived structures revealed that residues His435 and Trp457 act as a switch that mediates ligand activation. These residues show conservation for main chain (phi, psi) in His435 and moderate movement for Trp457. His435 in Heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Using the structure of the ligand-binding domain of the LXR receptor (1PQ8, 1PQ6, 1PQC, 1UPV) [61], two lignans that display all characteristics of high-affinity ligands, MR and Secoisolariciresinol esquilignan Diglycoside (SDG), have been identified. In cell-dependent assays, MR and SDG were able to activate the expression of several LXR regulated target genes, both in colon and in liver cells (personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Using the structure of the ligand-binding domain of the LXR receptor (1PQ8, 1PQ6, 1PQC, 1UPV) [61], two lignans that display all characteristics of high-affinity ligands, MR and Secoisolariciresinol esquilignan Diglycoside (SDG), have been identified. In cell-dependent assays, MR and SDG were able to activate the expression of several LXR regulated target genes, both in colon and in liver cells (personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, two residues play a crucial role in the molecular mechanism of LXRs action: the His435 at H11 and the Trp457 at H12 helices. Both steroidal and non steroidal ligands interact with His435, constraining its position and allowing a Tshaped aromatic-aromatic interaction with the Trp457 [22,23]. In this way, by interacting with the His435, agonist ligands indirectly promote the orientation of Trp457 to maintain the H12 in an agonistic state.…”
Section: Discussionmentioning
confidence: 99%
“…1 H NMR (500.13 MHz, CDCl 3 ) d H : 5.35 (1H, dt, J = 5.5 and 1.9 Hz, H-6); 4.33 (2H, q, J = 7.0 Hz, O-CH 2 CH 3 ); 3.53 (1H, tt, 10.6 and 4.9 Hz, H-3); 2.30 (1H, ddd, J = 12.9, 5.0 and 2.0 Hz, H-4b); 2. 23 13 To a solution of ester 9 (30.0 mg, 0.0600 mmol) in methanol (1 mL) and THF (1 mL), 5% aqueous LiOH (0.3 mL, 0.700 mmol) was added. The reaction mixture was stirred for 30 min at 25 C, diluted with water and concentrated to a third of its volume.…”
Section: Chemistrymentioning
confidence: 99%
“…Studies in vitro and in vivo have identified cholesterol derivatives including oxidized forms of cholesterol (oxysterols), cholesterol precursors (e.g., desmosterol) and plant sterols (e.g., stigmosterol) as endogenous LXR agonists that directly bind to the LXR ligand‐binding domain (LBD) . Binding of agonists to the LXR LBD mediates a conformational change largely driven by a mobile alpha helix at the carboxyl terminus (helix 12) that decreases the affinity of LXR for transcriptional corepressor proteins and increases the affinity for transcriptional coactivators . The transcriptional corepressors NCOR1 and NCOR2 (also referred to as the silencing mediator of retinoid and thyroid receptors; SMRT) are the major ligand‐dependent corepressors that interact with nuclear receptors.…”
Section: Dna Binding and Transcriptional Controlmentioning
confidence: 99%